2023
DOI: 10.3389/fpsyt.2023.1135923
|View full text |Cite
|
Sign up to set email alerts
|

The causal role of gastroesophageal reflux disease in anxiety disorders and depression: A bidirectional Mendelian randomization study

Abstract: BackgroundObservational studies have shown an association between gastroesophageal reflux disease (GERD) and anxiety disorders/depression. However, these evidences may be influenced by confounding factors. Therefore, our study aimed to determine the causal relationship between GERD and anxiety disorders/depression by conducting a bidirectional Mendelian randomization (MR) study.MethodsWe performed a bidirectional MR analysis using summary statistics from genome-wide association studies (GWAS) in European indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In relation to the sensitivity analyses, the meta-analysis findings based on the weighted median (OR = 1.33 [95% CI 1.17–1.48]; I 2 = 0.0%, P = 0.811) and MR-Egger regression (OR = 1.28 [95% CI 0.01–2.65]; I 2 = 4.8%, P = 0.305) methods were compatible with the primary results obtained from the IVW method. There was also a study by Zeng et al (17) that reported a direct causal effect of GERD on the risk of anxiety (OR = 1.35 [95% CI 1.15–1.59]).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…In relation to the sensitivity analyses, the meta-analysis findings based on the weighted median (OR = 1.33 [95% CI 1.17–1.48]; I 2 = 0.0%, P = 0.811) and MR-Egger regression (OR = 1.28 [95% CI 0.01–2.65]; I 2 = 4.8%, P = 0.305) methods were compatible with the primary results obtained from the IVW method. There was also a study by Zeng et al (17) that reported a direct causal effect of GERD on the risk of anxiety (OR = 1.35 [95% CI 1.15–1.59]).…”
Section: Resultsmentioning
confidence: 90%
“…A total of 4,537 publications were initially recovered by database searching, of which 4,501 were excluded because of duplication or unsuitability. Finally, 36 eligible studies were included in this systematic review and meta-analysis (7–11,13,14,17,18,22–48). The workflow of the search strategy and study selection have been illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of individuals with PPD typically experience recovery within a few months, although around 25-30% may still grapple with PPD a year following childbirth. 3 Suicide contributes to about 20% of postpartum fatalities, with 5-14% of pregnant and postpartum women reporting thoughts of suicide. 4…”
mentioning
confidence: 99%